2021
DOI: 10.1021/acsami.1c02501
|View full text |Cite
|
Sign up to set email alerts
|

Insulating and Robust Ceramic Nanorod Aerogels with High-Temperature Resistance over 1400 °C

Abstract: Ceramic aerogels, which present a unique combination of low thermal conductivity and excellent high-temperature stability, are attractive for thermal insulation under extreme conditions. However, most ceramic aerogels are constructed by oxide ceramic nanoparticles and thus are usually plagued by their brittleness and structural collapse at elevated temperatures (less than 1000 °C). Despite great progress achieved in this regard recently, it still remains a big challenge to design and fabricate intriguing ceram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 60 publications
1
36
0
1
Order By: Relevance
“…Studies so far have shown that the mechanical properties of ceramic aerogels can be considerably enhanced through elaborate structural engineering 1,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . For example, ceramic aerogels constructed from one-dimensional fibres can form a flexible porous framework by physical twining or chemical bonding, which can result in not only compression elasticity but also, more importantly, additional stretchability and bendability 21,22 .…”
mentioning
confidence: 99%
“…Studies so far have shown that the mechanical properties of ceramic aerogels can be considerably enhanced through elaborate structural engineering 1,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . For example, ceramic aerogels constructed from one-dimensional fibres can form a flexible porous framework by physical twining or chemical bonding, which can result in not only compression elasticity but also, more importantly, additional stretchability and bendability 21,22 .…”
mentioning
confidence: 99%
“…For ceramic aerogel, the thermal conductivity of polycrystalline structure is lower than that of single crystal structure, because in polycrystalline, the crystal grain size is small, there are many grain boundaries and defects. [71,72] The thermal conduction phonons are easy to scatter so the thermal conductivity is lower. As temperature rises, the difference becomes more pronounced.…”
Section: Mechanism Of High Temperature Resistancementioning
confidence: 99%
“…[1][2][3][4] These exceptional performances make ceramic aerogels attractive candidates for multi-applications such as thermal insulation, catalysis, filtration, environmental remediation, energy storage, etc. [5][6][7][8][9][10] However, conventional ceramic aerogels appear intrinsic brittleness in the process of shaping and machining, which is mainly due to the narrow neck connection of interparticle resorcinol-formaldehyde inks, in which a hydrochloric acid solution was applied to help inks to realize solidification. Yuan et al [25] fabricated 3D carbon aerogel micro-lattices via the fast freeze of deposited graphene oxide/polymer inks in a liquid nitrogen atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–4 ] These exceptional performances make ceramic aerogels attractive candidates for multi‐applications such as thermal insulation, catalysis, filtration, environmental remediation, energy storage, etc. [ 5–10 ] However, conventional ceramic aerogels appear intrinsic brittleness in the process of shaping and machining, which is mainly due to the narrow neck connection of interparticle in the pearl‐chain‐like networks. Thus, it remains challenging to obtain the custom‐designed architectures and geometries of ceramic aerogels based on subtractive manufacturing.…”
Section: Introductionmentioning
confidence: 99%